MANAJEMEN PEMAKAIAN MASKER SEBAGAI PERLINDUNGAN TERHADAP SDM UMKM KELOMPOK WANITA TANI (KWT) DAUN SALAM, KELURAHAN PAMULANG BARAT, KECAMATAN PAMULANG TANGERANG SELATAN DI MASA PANDEMI COVID-19 - Yayan Sudaryana; Susanto Susanto; Lisnawati Lisnawati; Tommi Santoso; Threesna Setyady; Corry Nata; Amilia Suryanita (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2021)
This service activity aims to provide knowledge and training to the community about mask wearing techniques and the benefits of using good masks, especially during this pandemic. The method used in this service report is the survey method and the delivery of material directly as well as simulations and discussions about the management of wearing masks as protection for human resources who are members of the Leaf Salam Women's Farmer Group UMKM. The conclusion of this community service is that all UMKM Members of the Daun Salam Women Farmer Group have understood and used masks properly and appropriately, so that self-protection against the Corona Virus or commonly known as Covid-19, becomes effective. Keywords: Masks, MSMEs, Covid-19